Institution building in weak states : the primacy of local politics - Radin, Andrew (Georgetown University Press, 2020)
"Andrew Radin challenges the accepted wisdom about the difficulties that foreign missions face when reforming state institutions in post-conflict societies. Rather than purging former elites and forcing democratic reform, Radin shows how working with elites, accounting for nationalist goals, and tempering or delaying reform objectives is more likely to produce enduring peace and stability. He examines the cases of Bosnia and Herzegovina, Kosovo, Iraq, and Timor-Leste, and compares them to a case of reform during an ongoing conflict in Ukraine. He focuses on reform efforts to the central government, defense sector, and police. Radin's domestic opposition theory offers a better explanation than either resources or path dependence as to why institution building fails. His work is based on field research in these countries and over 160 interviews. This is essential reading for scholars and practitioners of post-conflict missions, peacebuilding, and security"--